Hubungan Resiliensi, Self Efficacy Dan Depresi Dengan Manajemen Perawatan Diri Pada Pasien Diabetes Mellitus Dengan Ganggren Di Wilayah Kerja Puskesmas Besuki Kabupaten Situbondo - Lia Herlina; Alwin Widhiyanto; Iin Aini Isnawati (Universitas Katolik Widya Karya Malang, 2023)
Diabetes Mellitus is a chronic metabolic disorder with multiple etiologies characterized by high sugar levels. Patients with chronic illnesses are very susceptible to depression. This can be overcome if the respondent has good enough resilience and self-efficacy so that he can manage self-care and regulate glycemic levels and strive for better health. The aim of the research is to determine the relationship between resilience, self-efficacy and depression with self-care management in patients with diabetes mellitus in the Besuki Community Health Center working area. This research design is cross sectional/analytic correlation. The study population included 38 Diabetes Mellitus patients with Gangrene. The sampling technique uses probability sampling, total sampling. The sampling used was 38 people. The instrument uses a questionnaire sheet. And multiple linear regression statistical tests. The research results showed that the average resilience was 70.02, self-efficacy was 71, mild depression was 17 respondents and the average self-care management score was 72. Resilience increased self-care management with a p value of 0.000 ≤ α 0.005. Self-efficacy increases self-care management with a p value of 0.000 ≤ α 0.005 with an average coefficient of . the results of multiple linear regression obtained a p value of 0.000 ≤ α 0.005. There is a relationship between self-efficacy, resilience and depression with self-care management in patients with diabetes mellitus in the Besuki Community Health Center working area with a p value of 0.000 ≤ α 0.005 with a coefficient value of 0.608 so, Self-efficacy influences self-care 6 times more than other variables. Self-efficacy, good resilience can reduce depression in chronic patients such as gangrene so that patients have adequate self-care management.